History on trial: a study of the Salem commonage land claim - Bezuidenhout, GJW (Rhodes University, Faculty of Humanities, Department of History, 2020)
This thesis critically examines the Salem commonage claim, a dispute that has shaken the hamlet of Salem to its core. On ground level it has caused racialized fault lines to reopen, while suspicion and distrust has also grown between the black Africans of the area as well. On a national level, the Constitutional Court judgement has potentially set a precedent with regards to its jurisprudential approach in determining the validity of land claims in South Africa. Its interpretation of the law was determined by the restorative justice jurisprudence enshrined in the Restitution of Land Rights Act 22 of 1994 (the Act). It based its own understanding of the history of the commonage on this jurisprudence. In a bold step towards realising the aims and purposes of the Act, the Constitutional Court found that both the black African claimants as well as the white landowners have equal rights to the land. One of the reasons why the decision of the Constitutional Court is ground-breaking is that the dispute involves a former commonage "“ land used for common purpose. The Constitutional Court emphasised that the Act was an "extraordinary piece of legislation" and had to be interpreted in such a way so as to address the injustices of the past. This included provisions of the Act which dealt with how oral testimonies from claimants would be dealt with. Another interesting feature was the heavy reliance by all parties on expert witnesses in the persons of eminent historians, Professors Martin Legassick and Herman Giliomee. This case gave much-needed clarification as to what the appropriate role of an expert historian witness may be in a land claim. The success or failure of land claims often depend on the weight of the evidence supplied by the expert historian witness. But the historian must also take cognisance of the fact that the evidence s/he gives is appropriate according to the scope of law. This case also dismisses the assumption that colonial instruments of land assignation are beyond reproach. These instruments which grant rights to land may also be scrutinised in a court of law, just like when oral testimony is tested for its credibility. This is important to note, especially when balancing land rights of the claimants against those of the landowners. This thesis agrees with the decision taken by the Constitutional Court in this instance. However, it also cautions that such softly-softly approaches may appear as a suitable compromise on paper, but the feeling on the ground may not be as receptive to reconciliation as what the courts would have hoped for. To the jurist, this judgement accurately encapsulates the purpose and aims of the Act. However, such a judgement may not seem satisfactory to the people of Salem. The decisions of the Salem commonage case are sure to inform the discourse of land claims in South Africa.
Keywords: South Africa. Restitution of Land Rights Act, 1994; Salem (South Africa) -- History; Land tenure -- Law and legilstion -- South Africa; Land reform -- Law and legislation -- South Africa